Development of Small Scale Mould Stick Machine for Fish Cracker Production (Journal of Tropical Resources and Sustainable Science (JTRSS), 2017)
The usage of mould stick machines can be implemented to replace the manual hand kneading, rolling, shaping and cutting dough for fish crackers with the machine. The conventional method used manual hand kneading, rolling and shaping the dough of the fish cracker. This method takes time, need more manpower and reduce the quality of production. Therefore, the invention of machines helps producers to increase production quantity and quality by minimizing manpower. Besides that, this modern method may also help the producer to achieve the standard in terms of hygiene, safety and quality of these snacks. There are three common types of fish cracker mould stick machines used in markets such as rolling machines, conveyor machines and blowers machines. Therefore, this study aims to discuss the development and usage of mould stick machines for the fish cracker in improving its production in future.
Keywords: Types of machine; keropok lekor; conventional method; modern method; process